2015
DOI: 10.4209/aaqr.2014.10.0240
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach to Integrated Carbon Mineralization and Waste Utilization: A Review

Abstract: Carbon dioxide (CO 2 ) emission reduction in industry should be a portfolio option; for example, the carbon capture and utilization by mineralization (CCUM) process is a feasible and proven technology where both CO 2 capture and alkaline waste treatment occur simultaneously through an integrated approach. In this study, the challengeable barriers and significant breakthroughs of CCUM via ex-situ carbonation were reviewed from both theoretical and practical perspectives. Recent progress on the performance of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 100 publications
0
52
0
Order By: Relevance
“…It was also noted that a carbonation conversion of >85% for solid wastes should be acceptable to achieve waste stabilization and CO 2 fixation (Pan et al, 2015). Therefore, both economic and environmental benefits can be obtained by reducing the treatment cost of wastewater and increasing the added-value of bottom ash for construction materials through the application of the proposed CCU technology.…”
Section: Resultsmentioning
confidence: 99%
“…It was also noted that a carbonation conversion of >85% for solid wastes should be acceptable to achieve waste stabilization and CO 2 fixation (Pan et al, 2015). Therefore, both economic and environmental benefits can be obtained by reducing the treatment cost of wastewater and increasing the added-value of bottom ash for construction materials through the application of the proposed CCU technology.…”
Section: Resultsmentioning
confidence: 99%
“…The use of carbonated steelmaking slag as SCMs offers several benefits (Monkman et al, 2009;Pan et al, 2015a): (1) keep globally available industrial alkaline solid wastes out of landfills; (2) provide an economic approach to sequester CO 2 at the same time for construction use; (3) create an alternative source thereby reducing the need to transport suitable natural sands or the energy required to produce manufactured aggregates; (4) reduce the amount of leachable metals such as chromium after carbonation; and (5) reduce the amount of free CaO and its associated hydration expansion in service. Several studies have investigated the utilization of carbonated steel slag as SCMs in blended cement (Pan et al, 2015c) and a fine aggregate in concrete (Monkman et al, 2009).…”
Section: Utilization Of Carbonated Product As Supplementary Cementitimentioning
confidence: 99%
“…Carbonated industrial wastes such as steel slags, fly ash, bottom ash and cement kiln dust can also be used as construction aggregates. 2,10,11,23,28 In order to optimize the carbon mineralization technology, particularly ex situ schemes, various reaction parameters have been investigated ranging from particle size, porosity, reaction temperature and CO 2 pressure, solvent pH and chemical Annual production rate in the United States and average calcium and magnesium concentrations in fly ash, 2e9 cement kiln dust, 10,11 steel slag 12e20 and red mud 21,22 based on studies reported in Table 8.2. additives (e.g. chelating agents to enhance dissolution, or catalysts such as carbonic anhydrase to enhance CO 2 hydration).…”
Section: Introductionmentioning
confidence: 99%